Exploring the Management of Virtual Entrepreneurship at Boarding Vocational School during the COVID-19 Pandemic - Hardo Sujatmiko; Tri Joko Raharjo; Fakhruddin Fakhruddin; Tri Suminar (Universitas Negeri Semarang, 2021)
Entrepreneurial competence is one of the competencies that must be owned by vocational students. This scientific study article aims to explore the management of virtual entrepreneurship in boarding schools. The case study is at SMK Negeri Jateng Pati with 96 students and 3 entrepreneurial teachers. How to manage virtual entrepreneurial learning during Covid-19 pandemic at SMK Negeri Jateng in Pati? The data is obtained through semi-structured interview techniques and questionnaires on teachers and students. The data is analyzed using descriptive techniques and contextualized with the theory of project-based learning models. The findings of this study show that the management of virtual companies of vocational school students is less effective. The ownership of gadget, the availability of credit and network stability become obstacles to virtual entrepreneurial learning. Based on the results of the above research, it is recommended that there is a virtual entrepreneurial management practice model in boarding schools that implements Project-Based Learning (PjBL) model with order and turnover that can increase the students’ motivation to learn the practice and entrepreneurial competence.